-5(t-1)+t=5t-9

Simple and best practice solution for -5(t-1)+t=5t-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(t-1)+t=5t-9 equation:


Simplifying
-5(t + -1) + t = 5t + -9

Reorder the terms:
-5(-1 + t) + t = 5t + -9
(-1 * -5 + t * -5) + t = 5t + -9
(5 + -5t) + t = 5t + -9

Combine like terms: -5t + t = -4t
5 + -4t = 5t + -9

Reorder the terms:
5 + -4t = -9 + 5t

Solving
5 + -4t = -9 + 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
5 + -4t + -5t = -9 + 5t + -5t

Combine like terms: -4t + -5t = -9t
5 + -9t = -9 + 5t + -5t

Combine like terms: 5t + -5t = 0
5 + -9t = -9 + 0
5 + -9t = -9

Add '-5' to each side of the equation.
5 + -5 + -9t = -9 + -5

Combine like terms: 5 + -5 = 0
0 + -9t = -9 + -5
-9t = -9 + -5

Combine like terms: -9 + -5 = -14
-9t = -14

Divide each side by '-9'.
t = 1.555555556

Simplifying
t = 1.555555556

See similar equations:

| 5x^2+45x+70= | | x*2-6x-4=0 | | X(2x-5)+(3x+4)(6x-1)= | | 3x^2+42x+441=0 | | 73x-15=48+99 | | x+(x*.04)=2.75 | | (x+0.2)(x+3.9)=0 | | 28d+1=28 | | x^2+4x+28=0 | | x+x(.04)=2.75 | | 3(7-2h)=9 | | x^2=y-1 | | -s+3=52+21 | | x^2+34x+2= | | -x^2+565x-8250=0 | | (x-y)(x^2-10xy+y^2)=0 | | b-[x+4a+(x-7)]= | | 9+4+4v-2v+6=11 | | 15.6=2x-1.2 | | 80-2(p+1)=-20+48p | | .006x^3=6572 | | 3-2(2)-5=5(2)-22+3(2) | | 144=4q+4q | | 4x-3=3(-1+x) | | x+6forx=13 | | 120=p+7p | | 2x-3=-4+x | | 3x+(4x-1)=90 | | 0.1t=.4+.3t | | 8m+m=90 | | X+2x-1=2(-1+x) | | (4x^2-9x-9)= |

Equations solver categories